Ciclismo en Bogotá : factores que generan el cambio de modo de transporte a la bicicleta (2017)
This paper analyzes the factors associated with the increasing use of bicycles in Bogotá, Colombia. Studies on the use of bicycles in the United States and Europe expose diverse factors that facilitate its use, factors that promote the use of bicycles and factors that lead to the change of mode of transportation to the bike. In this article, emphasis was placed on this latter set of factors. The literature shows that congestion and the low cost of use of bike are some of the most determining factors when deciding to change to the bike. The question arises as to whether, in the case of Bogotá, the same thing happens as the literature presents. Around 400 surveys were conducted to study the behavior of cyclists in the city. These were carried out so that the sample surveyed was representative and significant. From the results obtained it was found that the factors...